(untitled) (Eurasian Journal of Ecology, 2018)
Scorzonera tau-saghyz Lipsch. et Bosse (tau saghyz) is rare endemic plant species of flora in Kazakhstan, which is included in the Red Book of the Republic of Kazakhstan. It is a strategic raw valuable species because it contains rubber in the root. The plant, first discovered in the Karatau Mountains, grows on stony and rocky slopes, low- and middle plateaus. In nature the plant is propagated by seeds and vegetatively by stem and root grafts. Hygrophill, frost and heat-resistant mesophyte plant has a wide range of environmental spectrum, wild forms are able to accumulate in the roots about 40% rubber. Rubber is contained in latex branches which penetrate roots, caudex and leaves of tau-saghyz. During the war from nature it seized more than 14 million plants and produced 902 tons of rubber for country’s defense industry. Restoration of its resources in a nature conditions is very slow due to the formation small amount of seeds to the 3-4-th year of vegetation period and seedling death at a young stage. One of the problems for large-scale cultivation of tau-saghyz is a low percentage of germination and seedling growth. The reason of this issue is the high susceptibility of seeds to various infections, impact of pests and physiologically low energy of seed germination. The aim of this research was to study the different modes of stratification and priming seeds of the wild plants tau-saghyz to increase the germination and sprouting of seeds and their subsequent reproduction to restore the number of population rare rubber plant species. It was found that the stratification of seeds at 70 C for 4 weeks and treatment by 0.1% thio-urea leads to a decrease of seeds contamination, increase the percentage of germination, as well as a large output of healthy seedlings of endemic plants Scorzonera tau-saghyz Lipsch. et Bosse. Key words: priming, propagation, Scorzonera tau-saghyz Lipsch. et Bosse, stratification, tau-saghyz.